2014
DOI: 10.1177/0265407514533767
|View full text |Cite
|
Sign up to set email alerts
|

Partner support for individual self-expansion opportunities

Abstract: Previous research indicates that partner responsiveness and self-expansion play key roles in the creation, maintenance, and improvement of close relationships. This experiment examined the hypothesis that active (vs. passive) partner support for an individual's opportunity for self-expansion would increase relationship satisfaction. In an experimental task manipulated to be either self-expanding or stressful, dating couple members (N ¼ 116; 58 couples) received active or passive support messages, ostensibly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Therefore, forecasting the outcomes of self-disclosure in unresponsive situations may prevent experiencing the negative consequences of partner unresponsiveness and may contribute to the relationship commitment. Experimental and daily-diary studies conducted among romantic couples supported this argument (Fivecoat, Tomlinson, Aron, & Caprariello, 2015;Gable, Reis, Impett, & Asher, 2004).…”
Section: Coping With Unresponsive Partnermentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, forecasting the outcomes of self-disclosure in unresponsive situations may prevent experiencing the negative consequences of partner unresponsiveness and may contribute to the relationship commitment. Experimental and daily-diary studies conducted among romantic couples supported this argument (Fivecoat, Tomlinson, Aron, & Caprariello, 2015;Gable, Reis, Impett, & Asher, 2004).…”
Section: Coping With Unresponsive Partnermentioning
confidence: 84%
“…Bu bulgulara göre, stres anında aktif bir destek görmeden partnerin yalnızca güvenini hissetmek dahi stresle başa çıkmak için yeterli olabilmektedir. Yine de aktif destek aktörlerin kendilerini geliştirmelerine yönelik etkinliklerde bulunabilmeleri açısından kritik bir öneme sahiptir (Fivecoat, Tomlinson, Aron ve Caprariello, 2015). Mutluluk paylaşımı çalışmaları da bu öneriyi destekler niteliktedir.…”
Section: Duyarsız Partner İlişkisiyle Başa çıKmaunclassified
“…Thus, one could argue that growth-oriented goals, promotion support, and personal movement toward the ideal self are expressed more in the early stages of a romantic relationship than in later years. However, Fivecoat et al (2015) cautioned against generalizing their findings, as no participants in their study were in a relationship longer than 5 years. Instead they suggested viewing their results as an initial indication.…”
Section: The Present Researchmentioning
confidence: 98%
“…It needs to be stressed that age correlates with relationship duration, and that relationship duration may also have an effect on self-expansion processes in the romantic domain (Fivecoat, Tomlinson, Aron, & Caprariello, 2015). While developmental research suggests that personal growth is of major importance for young adults (e.g., Havighurst, 1972), it has also been argued that personal development is particularly important during the early stages of a relationship (Mattingly, McIntyre, & Lewandowski, 2014).…”
Section: The Present Researchmentioning
confidence: 99%
“…Mitchell, Bartholomew, and Cobb showed that the higher was the partners' need-fulfillment in the relationship, the higher was their commitment to their marriage (13). Also, Fivecoat, Tomlinson, Aron, and Caprariello found that the relationship satisfaction increased more significantly in those who received active (instead passive) support for self-expansion (14).…”
Section: Introductionmentioning
confidence: 98%